Bioinformatics Analysis Reveals Crosstalk Among Platelets, Immune Cells, and the Glomerulus That May Play an Important Role in the Development of Diabetic Nephropathy - Yao, Xinyue; Shen, Hong; Cao, Fukai; He, Hailan; Li, Boyu; Zhang, Haojun; Zhang, Xinduo; Li, Zhiguo (Frontiers in Medicine, 2021)
Diabetic nephropathy (DN) is the main reason of end stage renal disease (ESRD). Glomerulus damage is one of the primary pathological changes in DN. To reveal the gene expression alteration in glomerulus involved in DN development, we screened the Gene Expression Omnibus (GEO)database up to December 2020. 11 gene expression datasets about gene expression of human DN glomerulus and its control were downloaded for further bioinformatics analysis. By using R language, all expression data were extracted and were further cross-platform normalized by Shambhala. Differentially expressed genes (DEGs) were identified by Student's t test coupled with false discovery rate (FDR) (P<0.05) and the fold change (FC)≥1.5. DEGs were further analyzed by the Database for Annotation, Visualization and Integrated Discovery (DAVID) to enrich the Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. We further constructed Protein-protein interaction (PPI) network of DEGs to identify the core genes. We used a digital cytometry CIBERSORTx to analyze the infiltration of immune cells in DN. 578 genes were identified as DEGs in this study. 13 were identified as core genes, in which LYZ , LUM and THBS2 were seldom linked with DN. Based on result on GO, KEGG enrichment and CIBERSORTx immune cells infiltration analysis, we hypothesize a positive feedback may form among glomerulus, platelets and immune cells. This vicious cycle may damage glomerulus persistently even after the initial high glucose damages were removed. To study those genes and pathway reported in this study may shade light on new knowledge of DN pathogenesis.